Magnetospheric responses to solar wind Pc5 density fluctuations: Results from 2D hybrid Vlasov simulation - Zhou, Hongyang; Turc, Lucile; Pfau-Kempf, Yann; Battarbee, Markus; Tarvus, Vertti; Dubart, Maxime; George, Harriet; Cozzani, Giulia; Grandin, Maxime; Ganse, Urs; Alho, Markku; Johlander, Andreas; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Ultra-low frequency (ULF) waves are routinely observed in Earth's dayside magnetosphere. Here we investigate the influence of externally-driven density variations in the near-Earth space in the ULF regime using global 2D simulations performed with the hybrid-Vlasov model Vlasiator. With the new time-varying boundary setup, we introduce a monochromatic Pc5 range periodic density variation in the solar wind. A breathing motion of the magnetopause and changes in the bow shock standoff position are caused by the density variation, the time lag between which is found to be consistent with propagation at fast magnetohydrodynamic speed. The oscillations also create large-scale stripes of variations in the magnetosheath and modulate the mirror and electromagnetic ion cyclotron modes. We characterize the spatial-temporal properties of ULF waves at different phases of the variation. Less prominent EMIC and mirror mode wave activities near the center of magnetosheath are observed with decreasing upstream Mach number. The EMIC wave occurrence is strongly related to pressure anisotropy and $β_\parallel$, both vary as a function of the upstream conditions, whereas the mirror mode occurrence is highly influenced by fast waves generated from upstream density variations.